RESPON TOKOH MUSLIM TERHADAP DEMOKRASI - Basman Basman (Jurnal Studi Islam, 2022)
Abstract: Democracy is seen as a political system and the best way of regulating life for every society that calls itself modern. Governments everywhere, including totalitarian regimes, try to convince the world community that they have a democratic political system. The discourse of democracy for most people, has become the dominant political discourse. That is why even the most authoritarian dictators must speak the language of democracy. Most Europeans think that the concept of Islamic democracy is such an antitheme that it is impossible to understand the appeal and power of Islamic movements. Because democracy is a concept that is still being debated, it is important to study how the perception of democracy among Islamic leaders in the recent era of the Islamic revival movement is. This type of research is library research, namely research in which the primary data source and secondary data source are literature. Data collection techniques were carried out by direct and indirect citations. The data analysis is carried out by content analysis, which is an effort to describe and analyze in depth the contents of a written or printed information objectively and systematically to reveal the message contained in it.This paper aims to describe the concept of democracy, the ways, attitudes and responses of Muslims to it. Can democracy be implemented and how far is the role of Islamic leaders in efforts to uphold democracy, or on the contrary, Islamic leaders hinder the democratization process.Abstrak: Demokrasi dipandang sebagai sistem politik dan cara pengaturan kehidupan terbaik bagi setiap masyarakat yang menyebut diri modern. Pemerintah di manapun, termasuk rejim-rejim totaliter, berusaha meyakinkan masyarakat dunia bahwa mereka menganut sistem politik demokratis. Wacana demokrasi bagi sebagian besar kalangan masyarakat, telah menjadi wacana politik yang dominan. Karena itulah para diktator yang paling otoriter sekalipun mesti berbicara dengan bahasa demokrasi. Kebanyakan orang Eropa menganggap bahwa konsep demokrasi Islam merupakan suatu antithema sehingga memustahilkan untuk memahami daya tarik dan kekuatan gerakan-gerakan Islam. Karena demokrasi merupakan konsep yang masih diperdebatkan, penting untuk dikaji bagaimana persepsi tentang demokrasi di kalangan tokoh-tokoh  Islam pada era gerakan kebangkitan Islam belakangan ini.Tipe penelitian ini adalah library research (penelitian pustaka), yaitu penelitian yang sumber data primernya dan sumber data sekundernya berupa literatur kepustakaan. Teknik pengumpulan data dilakukan dengan cara pengutipan lansung dan tidak lansung. Adapun analisis data ditempuh analisis isi, yaitu usaha menguraikan dan menganalisis secara mendalam isi suatu informasi tertulis atau tercetak secara obyektif dan sistematis untuk mengungkapkan pesan yang terkandung di dalamnya.Tulisan ini bertujuan untuk mendeskripsikan konsep demokrasi, cara, sikap dan respon umat Islam terhadapnya. Apakah demokrasi dapat diterapkan dan seberapa jauh peran para tokoh Islam dalam upaya menegakkan demokrasi, atau sebaliknya para tokoh Islam menghambat proses demokratisasi.